Beyond SiOx: an active electronics resurgence and biomimetic reactive oxygen species production and regulation from mitochondria. Issue 47 (26th November 2018) - Chang, Yao-Feng; Fowler, Burt; Chen, Ying-Chen; Lin, Chih-Yang; Xu, Gaobo; Huang, Hui-Chun; Chen, Jia; Kim, Sungjun; Li, Yi; Lee, Jack C.
Abstract : We explore overcoming the non-oxidizing environment requirement issues in silicon oxide (SiO x ) based memristors and investigate potential next steps for use of SiO x as a memristor material. Abstract : We explore overcoming the non-oxidizing environment requirement issues in silicon oxide (SiO x ) based memristors and investigate potential next steps for use of SiO x as a memristor material. A SiO x /HfO x stacked material was engineered, developed and tested to verify operation of the SiO x -based memristors, and the stacked material exhibits interfacial proton accumulation leading to ultra-low-voltage operation (<2 V). Also, a biomimetic self-recovery process (learning from the reactive oxygen species (ROS-like) production and regulation mechanism in mitochondria) has been demonstrated by a SiO x -based electrical device. The accumulative oxygen-induced ROS-like substance production in SiO x -based active electronics results in functional obstruction during the resistive switching transformation process, and further causes malfunction or a similar process to apoptosis (programmed cell death). The regulation system, also built-up by SiO x -based active electronics with neuromorphic learning, is designed for modulation of a ROS-like substance and provides an anti-ROS-like process to revive device functionality. The demonstrating of smart-material cycles in biomimetic self-recovery by SiO x -based active electronics represents critical milestones in future potential applications.